AKTUALISASI NILAI SPIRITUAL DALAM MENGHADAPI PANDEMI COVID-19 - Theguh Saumantri; Rifqi Ulinnuha (Jurnal Studi Hadis Nusantara, 2021)
The Covid-19 Virus pandemic, whose spread was massive and very difficult to handle. Various policies have been implemented by the government to break the chain of virus spreading. The government applies policies in various sectors that can trigger crowds. Because from the crowd and crowd that is the spread of the virus so quickly and massively. Until the government policy that causes controversy and also the pros and cons among Muslims is the absence of congregational prayers (five-time prayers, Friday prayers, tarawih prayers, and Eid al-Fitr prayers) in the mosque for a while. Some agree because it is for the common good to break the chain of the spread of the virus. And some disagree with the reason to reduce religious and spiritual values in worship. In this study, a conclusion will be found that spiritual values in human beings in the pandemic can remind ruhaniyahconsciousness to connect closely with great power, the values of immortality, finding the meaning of life and beauty.